The Influence of Training, Environment, and Motivation on Archivist Performance in Buleleng Regency - Gede Astutiyasa; Trianasari; I Nengah Suarmanayasa (Adisam Publisher, 2026)
Archiving is a crucial element in realizing accountable and transparent governance. However, internal archiving oversight of regional government agencies in Buleleng Regency indicates that some agencies have not yet achieved optimal performance, necessitating efforts to improve the performance of archivists. This study aims to analyze the influence of training, work environment, and motivation on the performance of archivists within regional government agencies in Buleleng Regency. This study uses a quantitative approach with multiple linear regression analysis method. The independent variables in this study are training (X1), work environment (X2), and motivation (X3), while the dependent variable is the performance of archivists (Y). The study population is Government Employees with Work Agreements (PPPK) who serve as archivists in regional apparatus within the Buleleng Regency Government. Data collection was carried out by distributing questionnaires using a Likert scale. The data obtained were analyzed through validity tests, reliability tests, classical assumption tests, and hypothesis testing using t-tests, F-tests, and coefficients of determination (R²). The results of the study indicate that training, work environment, and motivation simultaneously have a significant effect on the performance of archivists. Partially, training has no significant effect on performance, while work environment and motivation have a positive and significant effect. Motivation is the most dominant variable influencing performance. The coefficient of determination value of 0.734 indicates that 73.4% of the variation in archivist performance can be explained by these three variables, while the remainder is influenced by other factors outside the research model. These findings indicate that improving the performance of archivists needs to be focused on strengthening work motivation and improving a conducive work environment, accompanied by evaluating the effectiveness of training programs to make them more applicable and sustainable. Keywords: performance, training, work environment, motivation, archiving.